MINAT DAN MOTIVASI KEGEMARAN OLAHRAGA TERHADAP HASIL TES PEMANDUAN BAKAT SPORT SEARCH (Department of Physical Education, Sport, Health and Recreation, 2014)
Purpose of the study is to determine whether there is a correlation between interest and motivation to favorite sport against test results talent scouting sport fifth grade students of Public Elementary School 01 Sampangan Semarang in 2013?. Research methods using (1) the method of documentation used to obtain data on the names of members of the population, population in this study were fifth grade students of 01 Public Elementary School Sampangan Semarang totaled 77 students. (2) the questionnaire method to determine the interest and motivation of students favorite sports, and (3) test methods to determine test results modification sport scouting talent search. The results and discussion of the respondents have a high interest in sports favorite that is 51.95%, higher motivation in sports favorite that is as much as 49.35%, and the test results scouting talent search a good sport that is 74.03%, from statistical test analysis method simple correlation and multiple regression using a computerized processing system with SPSS, note that the probability that the value of> 0.5, which means significantly. Then the correlation of the results obtained by 0.743 means the level of interest and motivation to favorite sport there was a strong correlation with the test results scouting talent sport search and no direction is a positive correlation, meaning that the better the between interest and motivation to favorite sport against test results talent scouting sport searchÂ results will get better, and vice versa. Conclusion There is a significant correlation between interest and motivation to favorite sport against test results talent scouting sport fifth grade students of Public Elementary School 01 Sampangan Semarang in 2013 , and the advice from researchers ought to be reproduced again the method of early childhood talent in the field of sports not only excavated of physical factors alone but also from psychological factors, social and supporters.